'Don't say crap. Don't use swear words.' – Negotiating the use of swear/taboo words in the narrative mass media. (June 2019) - Bednarek, Monika
Abstract: This article uses a new corpus containing dialogue from 66 US television series to analyse the use of swear/taboo words in the narrative mass media. Swear/taboo words are both noticeable to audiences and associated with social attitudes and judgments, including language ideologies. They are also subject to regulations. At the same time, they have important functions for the narrative. Screenwriters must negotiate these competing demands and heed language-external constraints. In this article I examine how swear/taboo words are used in TV series and propose a new taxonomy of nine different linguistic practices.